2009
DOI: 10.1111/j.1753-6405.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

People, places and policies – trying to account for health inequalities in impoverished neighbourhoods

Abstract: Objective: We consider associations between individual, household and arealevel characteristics and self-reported health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…[29] Although, like us, Blackman et al[23] showed improvement in mental health after the urban renewal program, others have not been able to demonstrate this. [20-22] The most likely explanation is that compositional factors, which also have important influences on health,[30] are not, or are inadequately, addressed by urban renewal programs. Residents of neighbourhoods targeted for urban renewal often suffer from multiple deprivations, including poor housing conditions, and any interventions to improve health and well-being should also target other social determinants of health, for example, education and unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Although, like us, Blackman et al[23] showed improvement in mental health after the urban renewal program, others have not been able to demonstrate this. [20-22] The most likely explanation is that compositional factors, which also have important influences on health,[30] are not, or are inadequately, addressed by urban renewal programs. Residents of neighbourhoods targeted for urban renewal often suffer from multiple deprivations, including poor housing conditions, and any interventions to improve health and well-being should also target other social determinants of health, for example, education and unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 This is also true for Australia despite this country's relatively high overall wealth and the availability of free basic health care. [19][20][21] The reasons are complex and include practical barriers related to low income, 22 poor social resources, 23 poor health literacy, 24 perceived stigma, or previous unsatisfactory interaction with the medical system. 25 Our analyses used the residential address (postal code) at the time of clinic attendance to ascertain the Disadvantage Index.…”
Section: Found Anmentioning
confidence: 99%
“…Using qualitative and quantitative data from surveys of residents of 13 impoverished neighbourhoods in Victoria, this paper explores two related issues in order to develop improved understanding of potentially health‐impairing aspects of local physical and social environments: residents’ perceptions of their neighbourhood environments and their self‐reported health status. The paper builds on an analysis of the same data sets that suggested that contextual factors in neighbourhood environments may be contributing to differences in self‐reported health status between residents living in socially‐disadvantaged neighbourhoods and those living outside these neighbourhoods 19 . In this paper, we consider neighbourhood contexts of incivilities and disorders from two angles.…”
mentioning
confidence: 99%